2012
DOI: 10.7314/apjcp.2012.13.10.4867
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Cervical Cancer: An Emerging Therapeutic Target

Abstract: Cervical cancer is a leading cause of morbidity and mortality in women worldwide. Although the human papillomavirus (HPV) is considered the major causative agent of cervical cancer, yet the viral infection alone is not sufficient for cancer progression. The etiopathogenesis of cervical cancer is indeed complex; a precise understanding of the complex cellular/molecular mechanisms underlying the initiation, progression and/ or prevention of the uterine cervix is therefore essential. Autophagy is emerging as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…The induction of these two different types of autophagy may depend on different stimuli and cell types. Although the exact mechanisms of the two autophagy are not clear, it seems that the suppression of cytoprotective autophagy and the enhancement of cytotoxic autophagy might augment cytotoxic effects of anticancer drugs (Kanzawa et al, 2004;Takeuchi et al, 2005;Shingu et al, 2009;Pandey and Chandravati, 2012). In this study, we found that GA induced an apparent autophagy in GBM cells, and inhibition of autophagy could lead to enhancement of GA-mediated cytotoxicity through increasing apoptosis.…”
Section: Autophagy Inhibition Promotes Gambogic Acid-induced Suppressmentioning
confidence: 57%
“…The induction of these two different types of autophagy may depend on different stimuli and cell types. Although the exact mechanisms of the two autophagy are not clear, it seems that the suppression of cytoprotective autophagy and the enhancement of cytotoxic autophagy might augment cytotoxic effects of anticancer drugs (Kanzawa et al, 2004;Takeuchi et al, 2005;Shingu et al, 2009;Pandey and Chandravati, 2012). In this study, we found that GA induced an apparent autophagy in GBM cells, and inhibition of autophagy could lead to enhancement of GA-mediated cytotoxicity through increasing apoptosis.…”
Section: Autophagy Inhibition Promotes Gambogic Acid-induced Suppressmentioning
confidence: 57%
“…As a result, apoptosis-related molecules have been currently a major target of cancer therapies. However, autophagy induced by various chemotherapeutic agents can augment the anti-cancer potential of drugs (Pandey and Chandravati, 2012). The mode of autophagic action in cancer cells can be classified as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Although autophagy has been considered to be a cellular protective mechanism against cytotoxic agents (Eisenberg-Lerner and Kimchi, 2009), controversies regarding the roles of autophagy have recently emerged. Some researchers have suggested that the initiation of autophagy in response to chemotherapeutic agents functions as a cell death mechanism (Pandey and Chandravati, 2012). Moreover, crosstalk between autophagy and apoptosis can be complex and has seemingly contradictory roles that depend on the target cancer cell line or drug.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule-associated protein light chain 3 (LC3) protein is localized in autophagosomes and autolysosomes, the amount of LC3 II cleaved product is correlated with the extent of autophagosome formation, providing the marker for the detection of autophagic activity (Kabeya et al, 2000;Pandey and Chandravati, 2012). Class III PI3K is the homologue of Beclin 1, in this regulatory frame, Beclin 1 undertakes a central role because of its necessary function in the formation of autophagic vacuoles, and results in the occurrence of autophagy (Chen and Klionsky, 2011).…”
Section: Introductionmentioning
confidence: 99%